(untitled) (Economics and region, 2024)
The article explores the concept of green banking as a key tool for sustainable development and environmental transformation of the Ukrainian banking system. The authors emphasize the importance of introducing green banking technologies to ensure economic growth while minimizing the negative impact on the environment. The paper examines international experience in developing green banking, including lending instruments, green bonds, and asset securitization, which have effectively financed environmental projects. Particular attention is paid to the analysis of the dynamics of green bond issuance in different regions of the world, with Europe, the United States, and the Asia-Pacific region being the leaders. The paper provides data showing the rapid growth of sustainable investments, which reached USD 700 billion in 2023. It also highlights the key areas of use of green bond proceeds, such as energy, construction, transport, and waste management. The study analyzes in detail the peculiarities of green banking development in Ukraine, in particular its role in the post-war economic recovery. The authors emphasize that the introduction of green banking initiatives can help attract foreign investors, create jobs in the environmental infrastructure sector, and develop innovative technologies. The importance of green lending as a tool to support energy efficiency and renewable energy projects is highlighted. Among the main challenges to the implementation of green banking in Ukraine are low customer awareness, economic instability, lack of a clear state policy, and high start-up costs for the introduction of innovations. The authors propose comprehensive approaches to addressing these challenges, including conducting information campaigns, developing incentives for banks and customers, and adapting international experience. The findings emphasize that green banking is a powerful tool for building a sustainable economic future for Ukraine. A comprehensive approach to the implementation of this concept will not only contribute to the economic recovery after the war but also to the formation of an environmentally sustainable financial environment that meets the best international practices.